Crystal growth in gelled solution: applications to coordination polymers. Issue 14 (15th March 2016) - Rizzato, Silvia; Moret, Massimo; Merlini, Marco; Albinati, Alberto; Beghi, Fabio
Abstract : By using a gel method to grow crystals of coordination polymers, some interesting phenomena have been observed. Among these are some characteristic micro- and macroscopic modifications of the crystalline solids and the incorporation of a gel matrix inside the crystals. Abstract : Some critical issues concerning the complex synthesis and crystallization of designed coordination polymers are highlighted by using gels as diffusion media. The systematic use of gel methods in a variety of different crystallization configurations has been proven useful in revealing the field of existence and the stability hierarchy of competitive and concomitant crystalline phases, and also in discovering some important effects due to gel matrices. The most interesting phenomena observed are the modification and alteration of the macro- and microscopic morphology of crystals due to gel incorporation, which are responsible for changes in many properties and functionalities of these materials, opening up new possibilities for their applications in a variety of technological fields. In addition, a kinetic study of a gel grown polymeric system has also been conducted, demonstrating the continuous evolution of crystal morphology and its connection with the crystal growth process and growth mechanism.